Systemic Inflammatory Responses and Lung Injury following Hip Fracture Surgery Increases Susceptibility to Infection in Aged Rats - Hao Zhang; Tiansheng Sun; Zhi Liu; Jianzheng Zhang; Xiaowei Wang; Jia Liu (Mediators of Inflammation)
Pulmonary infections frequently occur following hip fracture surgery in aged patients. However, the underlying reasons are not fully understood. The present study investigates the systemic inflammatory response and pulmonary conditions following hip fracture surgery as a means of identifying risk factors for lung infections using an aged rodent model. Aged, male Sprague-Dawley rats (8 animals per group) underwent a sham procedure or hip fracture plus femoral intramedullary pinning. Animals were sacrificed 1, 3, and 7 days after the injury. Markers of systemic inflammation and pulmonary injury were analyzed. Both sham-operated and injured/surgical group animals underwent intratracheal inoculation with Pseudomonas aeruginosa 1, 3, and 7 days after surgery. P. aeruginosa counts in blood and bronchoalveolar lavage (BAL) fluid and survival rates were recorded. Serum TNF-α, IL-6, IL-1β, and IL-10 levels and markers of pulmonary injury were significantly increased at 1 and 3 days following hip fracture and surgery. Animals challenged with P. aeruginosa at 1 and 3 days after injury had a significantly decreased survival rate and more P. aeruginosa recovered from blood and BAL fluid. This study shows that hip fracture and surgery in aged rats induced a systemic inflammatory response and lung injury associated with increased susceptibility to infection during the acute phase after injury and surgery.